Forecasting Number of Truck Drivers on Road Network in Eastern Economic Corridor of Thailand by Using 4-Steps Sequential Decision Models - Buakla, Apichat; Sangsrichan, Chaiwat; Pochan, Jessada (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2022)
This article proposes an approach to forecasting the number of truck drivers on the road network in the Eastern Economic Corridor (EEC) of Thailand. The forecasting model of freight transportation was developed according to the academic principles of traffic and transportation engineering by 4-step sequential decision model. The method was divided into four steps: 1) collecting data for model development, 2) developing the model, 3) calibrating the model, and 4) applying the model. The results revealed that the freight forecasting outcomes obtained from the 4-steps sequential decision models differed between the cases with and without the EEC development. In the case of the EEC development, the total cargo volume in all modes of transportation (road, railway, water, air) was forecasted approximately at 3,217.43 thousand tons/day in 2051. Most of them were road transport, about 97.98 % with other modes accounting for 2.02 % only. The 4-wheeler mini truck had the largest share, about 63.58 %, followed by 6-wheel medium trucks, trailers, 10-wheel trucks, and semi-trailers, which accounted for 12.09, 8.70, 8.02, and 7.61 %, respectively. Furthermore, the number of truck drivers was forecasted to increase from 52,791 persons (2021) to 74,153 persons in 2051, which was high compared to the case without EEC development of about 2,227 persons.